1993
DOI: 10.1203/00006450-199304000-00016
|View full text |Cite
|
Sign up to set email alerts
|

Group A Rotaviruses Produce Extrahepatic Biliary Obstruction in Orally Inoculated Newborn Mice

Abstract: Extrahepatic biliary atresia is a devastating disease occurring in 1 in 10,000 to 14,000 infants annually in the United States. We have recently described preliminary data suggesting an association of group C rotavirus with biliary atresia in two infants. However, a group C rotavirus animal model of biliary atresia is not presently available. On the other hand, some strains of the better-characterized and much more common group A rotaviruses produce hepatobiliary disease in infant mice. This disease shares man… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
164
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 146 publications
(172 citation statements)
references
References 15 publications
8
164
0
Order By: Relevance
“…1d). This finding was consistent with the original report of this model by Riepenhoff-Talty et al [12], in which RRV was cleared in neonatal mice between the 1st and 2nd week post infection.…”
Section: Rotavirus Infection Causes Biliary Obstruction and Growth Fasupporting
confidence: 93%
See 3 more Smart Citations
“…1d). This finding was consistent with the original report of this model by Riepenhoff-Talty et al [12], in which RRV was cleared in neonatal mice between the 1st and 2nd week post infection.…”
Section: Rotavirus Infection Causes Biliary Obstruction and Growth Fasupporting
confidence: 93%
“…That study demonstrated that the portal tract inflammation which was unique to BA was composed of a CD4 + Th1 cell predominant process, characterized by an infiltrate of CD4 + and CD8 + T cells and macrophages with local cellular production of IL-2, IFN-γ and TNF-α. In order to better understand the kinetics of the pathologic immune events in BA, we are utilizing the rotavirus-induced murine model of BA [12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…A wide range of enteric viruses has been implicated including REOvirus and cytomegalovirus (CMV) but clinical evidence of exposure and its relevance is conflicting whether derived from serological studies (7,8,9) or more directly from PCR studies on liver biopsies to detect viral nucleic acids (10).…”
Section: Introductionmentioning
confidence: 99%